Research on visual design of urban multimedia portal - Lin Wang; Minghui Zhu; Yi Zhang (Scientific Reports)
Abstract In the digital multimedia era, city portal websites significantly impacted urban identity representation. This study addresses the complex challenge of selecting color schemes that authentically reflect cities’ unique characteristics. We developed a decision model integrating Fuzzy Analytic Hierarchy Process and Gray Relational Analysis (FAHP-GRA) to evaluate color preferences. Analysis of 130 portal websites revealed blue (0.1386) and green (0.0980) schemes achieved the highest preference ratings, with significant variations across cultural backgrounds, age groups, and genders. Japanese users preferred white/green interfaces, Germans favored blue/green, while Chinese showed stronger preferences for green/red designs. The FAHP-GRA approach demonstrated 83.5% prediction accuracy, significantly outperforming traditional methods. This model provides designers with evidence-based guidance for creating culturally resonant interfaces through informed color selection, enhancing both creativity and user engagement. The findings contribute to the development of more effective visual communication strategies for urban digital presence.